2018
DOI: 10.1007/s12250-018-0045-y
|View full text |Cite
|
Sign up to set email alerts
|

Tandem 3′ UTR Patterns and Gene Expression Profiles of Marc-145 Cells During PRRSV Infection

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) causes substantial economic losses to the global pig industry. Alternative polyadenylation (APA) is a mechanism that diversifies gene expression, which is important for tumorigenesis, development, and cell differentiation. However, it is unclear whether APA plays a role in the course of PRRSV infection. To address this issue, in this study we carried out a whole-genome transcriptome analysis of PRRSV-infected Marc-145 African green monkey kidney cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…mRNA profiles were also investigated in many previous studies, and several tissues and cells were found to be prone to damage caused by PRRSV, such as peripheral blood mononuclear cells (15), lung dendritic cells (36), Marc-145 cells (37), and lung tissues (34). Discrepancies among the differentially expressed mRNAs identified in previous studies may be due to differences in pig breeds and PRRSV strain.…”
Section: Discussionmentioning
confidence: 99%
“…mRNA profiles were also investigated in many previous studies, and several tissues and cells were found to be prone to damage caused by PRRSV, such as peripheral blood mononuclear cells (15), lung dendritic cells (36), Marc-145 cells (37), and lung tissues (34). Discrepancies among the differentially expressed mRNAs identified in previous studies may be due to differences in pig breeds and PRRSV strain.…”
Section: Discussionmentioning
confidence: 99%
“…More than half of mammalian genes are characterized by alternative polyadenylation of their transcripts [ 12 , 13 ]. Various biological effects associated with tandem APA were investigated, including cancer transformation, embryonic development, immune responses, neuronal activity [ 12 , 14 ] as well as virus–host interaction [ 15 17 ]. In this study, we used in vitro transcription sequencing alternative polyadenylation sites (IVT-SAPAS) method to profile differential APA site switching events and differentially expressed genes in IPEC-J2 cells during the infection of PEDV variant strain GDS01.…”
Section: Introductionmentioning
confidence: 99%
“…Although virus isolation is difficult, it can be attempted from the ascitic fluid, serum, and tissues (spleen, tonsils, lungs, and lymph nodes). All diagnoses of PRRS are complicated by the inability to detect virus particles in pigs [ 17 18 ].…”
Section: Introductionmentioning
confidence: 99%